Review of the genus Eridolius Förster from the Oriental Region (Hymenoptera, Ichneumonidae, Tryphoninae) - Reshchikov, Alexey (Zootaxa, 2018)
The Oriental species of the genus Eridolius Förster, 1869 are reviewed, and a new species, E. xui Reshchikov, sp. nov. is described from Southern China. This is the seventh record of the genus from the Oriental region. The new species can be distinguished from all other Oriental species of the genus by its lower mandibular tooth longer than upper one, face entirely black, and coxae, hind femur and most of metasoma reddish. An illustrated key to the Oriental species of the genus is provided. Eridolius guptai is recorded for the first time from Lao and E. niger is recorded for the first time from Arunachal Pradesh (India).